Avaliação dos benefícios da adoção de boas práticas de manejo no bem-estar de bezerros leiteiros - Magalhães Silva, Lívia Carolina [UNESP] (2015)
The aims of this study were to evaluate the adoption of good practices of handling effects on dairy calves welfare, and to evaluate the specific effects of the mother's presence in the first 24 hours and the tactile stimulation in these animals. Therefore, we carried out two experiments, Experiment 1 were evaluated 48 male calves crossed (Holstein x Gir x Jersey) and the Experiment 2, 48 calves female Girolando breed. In both experiments, the calves were watching from birth to the 120 days of age. In the Experiment 1, were adopted handling groups: Control Handling (dairy calves in tropical houses during whole suckling period using abrupt weaning) and the Good Practice of Handling (GPH), composed by suckling in teats buckets, opportunity for to express social behaviour, positive interaction human-calf, tactile stimulation and gradual weaning). Experiment 2 consisted of four handling groups, all the calves were handling with GPH, evaluating the effects of the mother's presence in the first 24 hours and tactile stimulation until weaning, to knowledge: MH = the calves had the mother's presence in the first 24 hours of life; MSH = as MH, but with the adoption of tactile stimulation; OH = calves were separated immediately from mother after birth (without any contact with cow); OSH= as OH, but with the adoption of tactile stimulation. To evaluate the dairy calves' welfare, in both studies, were considered the health, physiological, behavioral and performance indicators. The effects of handling groups on animal welfare indicators were evaluated with normal distribution using analysis of variance (ANOVA) with repeated measures using the restricted maximum likelihood (REML) by the MIXED procedure of SAS. Means were compared by the Tukey test, with P values <0.10 for deletion and P <0.05 for significance. For the welfare's indicators presented binomial distribution was used the method of restricted maximum likelihood (REML), with application ...